2014
DOI: 10.1007/s11095-014-1559-0
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Pharmacokinetics of Thermosensitive Stealth® Liposomes Encapsulating 5-Fluorouracil

Abstract: Complexation of 5-FU with copper-polyethylenimine appears an interesting strategy to improve 5-FU retention into TSLs in vitro and in vivo. TSLs allow heat-triggered release of the drug within 10 min at 42°C, a reasonable time for future in vivo experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In this study, a frequency of 1 MHz was chosen because of its use in numerous therapeutic treatments [5]. More precisely, sonoporation and the triggered release of thermosensitive liposomes (TSLs) [28] were targeted. Whereas sonoporation generally requires a relatively low peak negative pressure (PNP), the mild hyperthermia required to reach the melting phase transition temperature of the TSLs is more challenging to generate at 1 MHz: [29] showed that this temperature, typically approximately 42˚C, can be reached at 1 MHz, More detailed information about the design stage, the manufacturing process and the choice of the CMUT geometry are given by [27].…”
Section: Overview Of the Usgfus Cmut Probementioning
confidence: 99%
“…In this study, a frequency of 1 MHz was chosen because of its use in numerous therapeutic treatments [5]. More precisely, sonoporation and the triggered release of thermosensitive liposomes (TSLs) [28] were targeted. Whereas sonoporation generally requires a relatively low peak negative pressure (PNP), the mild hyperthermia required to reach the melting phase transition temperature of the TSLs is more challenging to generate at 1 MHz: [29] showed that this temperature, typically approximately 42˚C, can be reached at 1 MHz, More detailed information about the design stage, the manufacturing process and the choice of the CMUT geometry are given by [27].…”
Section: Overview Of the Usgfus Cmut Probementioning
confidence: 99%
“…Mild heating of a tumor (41 – 43°C for 10 – 60 min) may improve the therapeutic efficacy of drugs by acting on tumor hemodynamics ( Figure 3 ): (i) by increasing tumor perfusion, thus enhancing drug bioavailability in tumor tissue ( Song, 1984 ); (ii) by increasing vascular permeability ( Lefor et al, 1985 ; Kong et al, 2001 ) and reducing tumor interstitial pressure ( Vaupel and Kelleher, 2012 ), leading to better drug penetration within tumor tissue. In addition, local heating can act as an external trigger for drug release from a carrier, e.g., thermosensitive nanoparticles ( Yatvin et al, 1978 ; Lindner et al, 2004 ; Manzoor et al, 2012 ; Hijnen et al, 2014 ; Al Sabbagh et al, 2015 ). Ultrasound can also generate directional ARF on molecules along its propagation path ( Sarvazyan et al, 2010 ; Figure 3 ).…”
Section: Microbubble-assisted Ultrasoundmentioning
confidence: 99%
“…Currently DOX is only occasionally used in the clinic as a radiosensitizer in the treatment of soft tissue sarcomas, hence a soft tissue sarcoma cell line (HT1080) was used in this study. In contrast, other radiosensitizers, which are also chemotherapeutic agents, exist which are more commonly used in the clinic and are already encapsulated in a TSL, including cisplatin [ 46 ], pyrimidine analogue gemcitabine (dFdC) [ 47 ] and 5-FU [ 48 ]. However, the objective of these studies is to decrease the toxicity of the chemotherapeutic agent by TSL encapsulation, and as a consequence have not been tested as a radiosensitizer for triggered local release in combination with RT.…”
Section: Discussionmentioning
confidence: 99%